Regulatory effects of chloride on mineral element uptake, fruit yield and quality in kiwifruit plants - FAN Xiaodong; XUE Ziyue; XU Kaiwei; FAN Peng; ZHAO Shuguang; WANG Xiaoling; CHEN Yuanxue (Guoshu xuebao)
[Objective] The chloride requirement of kiwifruit is more than 10 times that of other crops. However, irrational application of chloride-containing fertilizers in kiwifruit production and easy leaching of chloride ions from orchard soil have resulted in kiwifruit being prone to chloride deficiency, which seriously restricts kiwifruit vine growth as well as yield and fruit quality improvement. Chloride application can improve plant photosynthesis, nutrient absorption, fruit yield and quality. Therefore, this experiment aimed to investigate the effects of application of different concentrations of chloride fertilizers on the photosynthetic characteristics, mineral element absorption, and fruit yield and quality of kiwifruit plants. [Methods] The experimental site was located in the main kiwifruit planting area of Mianzhu City, Sichuan Province. The material for this experiment was selected as Hongshi No.2 kiwifruit, and the rootstock was wild kiwifruit from the Delicious line, which was planted in 2014 and was an adult bearing vine in full production. Four chloride level treatments (0 kg·hm-2, 90 kg·hm-2, 180 kg·hm-2, and 360 kg·hm-2) were set up, and the amount of nitrogen, phosphorus and potassium was the same in each treatment. Fertilizers (basal fertilizer, sprouting fertilizer, pre-flowering fertilizer, fruit-promoting fertilizer, fruit-expanding fertilizer and quality-enhancing fertilizer) were applied six times throughout the year. Fertilizer was applied by spraying water after spreading to promote the dissolution of fertilizer into the infiltrated root layer. This test was conducted in a positional manner for 2 consecutive years (2022 and 2023). Leaf net photosynthetic rate, chlorophyll a, chlorophyll b, and total chlorophyll contents were measured at the fruiting stage. The dry matter contents of different parts of kiwifruit (new shoots, leaves, and fruits) and the mineral contents in leaves (nitrogen, phosphorus, potassium, chloride, calcium, magnesium, iron, manganese, and zinc) were determined at harvest. Fruit yield and fruit grading were measured during harvest, and the appearance quality (single fruit weight, longitudinal diameter, transverse diameter, and fruit shape index) was measured after fruit picking, and the intrinsic quality (soluble solids, titratable acid, vitamin C, and soluble sugar) was measured after soft ripening. [Results] Leaf chlorophyll a (Chl a), total chlorophyll content (Chl) and net photosynthesis rate (Pn) showed a tendency to increase and then decrease with the increase of chloride application level, and Cl-180 treatment had the best effect. Compared with no chloride treatment, leaf chlorophyll a content (Chl a), total chlorophyll content (Chl) and net photosynthetic rate (Pn) of Cl-180 treatment increased by 10.73%, 11.55% and 4.43%, respectively. Comprehensive analysis of the 2-year experiment revealed that chloride application could significantly increase leaf chloride content, and enhance kiwifruit leaf mineral nutrient contents. Compared with the non-chlorination treatment, the annual average nitrogen (N), potassium (K2O), magnesium (Mg), and iron (Fe) contents with the Cl-180 treatment were higher by 14.64%, 36.27%, 14.38%, and 42.34%, respectively; but the Cl-360 treatment significantly reduced the phosphorus (P2O5) content. Chloride application significantly increased kiwifruit yield. Compared with non-chloride treatment, chloride application increased the yield by 0.68%-14.65% per year on average, and the optimum chloride application rate was fitted to 164.0 kg·hm-2. Chloride application significantly increased the rate of large fruits in kiwifruit. Compared with the non-chloride treatment, the Cl-180 treatment increased large fruit size by 10.48% and reduced small fruit size by 9.41%, respectively, on an annual average. Chloride application significantly affected the dry matter accumulation and distribution ratio of kiwifruit. Dry matter accumulation with the Cl-180 treatment increased by an annual average of 15.38% compared with the non-chlorination treatment. The overall dry matter distribution ratio among kiwifruit parts was: fruit (57.59%-63.19%) > new shoots (26.36%-31.41%) > leaves (10.30%-13.33%). The combined 2-year results showed that the Cl-180 treatment promoted an increase in the proportion of dry matter allocation to fruits and branches compared to the non-chloride treatment. The 2-year experiment revealed that the single fruit weight of kiwifruit increased and then decreased with increasing levels of chloride application, and the single fruit weights with the Cl-90 and Cl-180 treatments were significantly higher than those of the non-chloride treatment. Chloride application significantly improved the intrinsic quality of kiwifruit fruit. The two-year experiment showed that the soluble sugar content (SS), soluble solids content (SSC) and solid-acid ratio (SSC/TA) of kiwifruit fruits tended to increase and then decrease with increasing levels of chloride, and the best effect was observed in the Cl-180 treatment. Compared with non-chloride treatment, the soluble sugar content (SS), soluble solids content (SSC), and solid-acid ratio (SSC/TA) in Cl-180-treated fruits increased by 12.16%, 12.75%, and 23.06%, respectively, and the titratable acid (TA) content decreased by 8.80%. Further analysis of the main controlling factors affecting quality among different chloride treatments showed that, compared with Cl-0 treatment, Cl-90 treatment promoted fruit quality by significantly increasing leaf N and increasing sugar and decreasing acidity, while Cl-180 treatment increased fruit sugar significantly increasing leaf N, Mg, and Chl. Cl-360 treatment mainly decreased the absorption of leaf P2O5 and Fe, and affected the fruit yield and quality. [Conclusion] Reasonable chloride application can increase the chlorophyll and photosynthetic characteristics of kiwifruit, promote the absorption and utilization of mineral elements, and further affect the vine growth as well as increase the rate of large fruit and yield, and improve the fruit quality. In addition, our results indicated that the economic yield of kiwifruit could be maximized when the chloride application rate was 164.0 kg·hm-2.